Nutritional influences on gut physiology and microflora in the post-weaned piglet - Pickard, Julie Anne (2003)
In piglets, the post-weaning growth check is commonly associated with the weaning process that occurs within the European Union at approximately 3-4 weeks of age. The aims of the studies reported here were to investigate the contribution and importance of nutritional influences on the complex and multi-factorial problem of the post-weaning growth check in the piglet. Multi-disciplinary investigations focussed upon the relationship between post-weaning nutrition and the gut ecosystem with specific emphasis on gut physiology, immunity and microflora.